2016
DOI: 10.3892/ol.2016.4253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-1β and tumor necrosis factor α gene silencing on mouse gastric cancer cell proliferation and migration

Abstract: Abstract. The aim of the present study was to investigate the effect of interleukin-1β (IL-1β) and tumor necrosis factor α (TNFα) gene co-silencing in mouse gastric cancer (GC) cells. Respectively, three pairs of liposome-encapsulated IL-1β and TNFα small interfering RNA (siRNA) were transfected into the mouse GC cell line MFC. The most effective siRNA, as identified by reverse transcription-polymerase chain reaction, was used for co-suppression of IL-1β and TNFα genes. The activities of cell proliferation, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…According to research on renal cell carcinoma, small doses of TNF-α in the tumor microenvironment can enhance tumor cell proliferation, invasion, and metastasis, increase white blood cells, form blood vessels, and induce upregulation of other cytokines (e.g., angiogenesis factor and matrix metalloproteinases), and trigger epithelial-mesenchymal transition (EMT) of tumor cells [ 7 ]. In addition, an animal experiment also found that silencing the TNF-α gene can inhibit the proliferation and migration of gastric cancer cells [ 8 ]. Nevertheless, how TNF-α promotes invasion and metastasis of tumor cells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to research on renal cell carcinoma, small doses of TNF-α in the tumor microenvironment can enhance tumor cell proliferation, invasion, and metastasis, increase white blood cells, form blood vessels, and induce upregulation of other cytokines (e.g., angiogenesis factor and matrix metalloproteinases), and trigger epithelial-mesenchymal transition (EMT) of tumor cells [ 7 ]. In addition, an animal experiment also found that silencing the TNF-α gene can inhibit the proliferation and migration of gastric cancer cells [ 8 ]. Nevertheless, how TNF-α promotes invasion and metastasis of tumor cells is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IL-6 is a pivotal target of metformin that can inhibit cancer growth and metastasis [17]. The inhibition of IL-1β and IL-18 by metformin also plays an important role in suppressing gastric tumorigenesis because IL-1β can stimulate gastric cancer cell proliferation and IL-18 can facilitate gastric cancer cell immune escape [44,45]. In addition, TNF-α, which induces insulin resistance in type 2 diabetes, also promotes gastric cancer proliferation, migration, and invasion [44].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of IL-1β and IL-18 by metformin also plays an important role in suppressing gastric tumorigenesis because IL-1β can stimulate gastric cancer cell proliferation and IL-18 can facilitate gastric cancer cell immune escape [44,45]. In addition, TNF-α, which induces insulin resistance in type 2 diabetes, also promotes gastric cancer proliferation, migration, and invasion [44]. Our study shows that expression of TNF-α mRNA is decreased by 62 % in db/ db mice treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ability of OSCC to invade and metastasize or be enhanced by the presence of inflammatory mediators [ 46 , 47 ], TNF-α is worthy of particular attention in OSCC, with its presence demonstrated to enhance cell proliferation and its downregulation demonstrated to inhibit proliferation and migration in other carcinomas, both in vitro [ 48 ] and in vivo animal models [ 49 ].…”
Section: The Role Of Tnf-α In the Promotion Of Osccmentioning
confidence: 99%